2022
DOI: 10.20885/ijca.vol5.iss1.art3
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kandungan Mineral dari Lumpur Panas Sidoarjo sebagai Potensi Sumber Silika dan Arah Pemanfaatannya

Abstract: Lumpur panas Sidoarjo merupakan salah satu bencana luapan lumpur panas yang memiliki dampak signifikan di Indonesia terhitung sejak 29 Mei 2006. Adanya bencana ini banyak menimbulkan kerugian kesehatan, lingkungan hingga ekonomi. Akan tetapi,dibalik kerugian tersebut ternyata terdapat banyak kandungan mineral dalam lumpur luapan yang dapat dimanfaatkan sebagai contoh silika. Tujuan penelitian ini adalah mengetahui kandunganmineral terutama silika dalam lumpur panas Sidoarjo yang dapat berpotensi sebagai sumber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Based on the results of a simple quantitative analysis using Match 3 calculations, the SiO 2 quartz phase is the most dominant phase in the Sidoarjo mud sample with position 2θ = 26.73 o . whereas according to JCPDS data (01-085-0797), the SiO 2 diffraction pattern at 2θ for the main peak is 20.857; 26.64; 36,542; 39.75; 50,141; 59,953; 68,147 [ 35 ]. The data shows the same pattern as this research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of a simple quantitative analysis using Match 3 calculations, the SiO 2 quartz phase is the most dominant phase in the Sidoarjo mud sample with position 2θ = 26.73 o . whereas according to JCPDS data (01-085-0797), the SiO 2 diffraction pattern at 2θ for the main peak is 20.857; 26.64; 36,542; 39.75; 50,141; 59,953; 68,147 [ 35 ]. The data shows the same pattern as this research.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, sodium silicate extraction was carried out because sodium silicate and its derivatives have various benefits in industry. The silicate content in Sidoarjo mud is very high, namely 45.3% [ 34 , 35 ], this can be an alternative source of raw materials for silicate production, increasing the economic value of a material and preliminary studies to determine suitable technology for the extraction of valuable metals in Sidoarjo mud. To achieve this goal, two stages were carried out, namely the decomposition of silicate from the Sidoarjo mud with the addition of Na 2 CO 3 and water leaching to dissolve the sodium silicate formed.…”
Section: Introductionmentioning
confidence: 99%
“…The Lapindo mud reported that the Lapindo mud contains oxide compounds such as aluminum oxide, silicon dioxide, potassium oxide, titanium oxide, calcium oxide, manganese oxide, phosphorus pentoxide, sulfur oxide, vanadium pentoxide, and others [1]. in a different study similar findings regarding the mineral composition contained in the Lapindo mud [2].…”
Section: Introductionmentioning
confidence: 81%
“…The results of the XRF analysis of Sidoarjo Mud samples can be presented in Table 2. Source: [20] The largest abundance of elements in the mud content of Lusi Island is silicon elements, with a percentage of 31.1%. The diversity of this metal element has many potentials and directions of use that are so wide that it can be used as a useful and appropriate product for human life; for example, it is used as a cat alyst, heavy metal adsorption, and water purification [20][21].…”
Section: Condition Of the Lusi Island Mangrove Ecosystemmentioning
confidence: 99%